Combining Various Methods to Assess Insulin Sensitivity in Nonobese Rat after Sleeve Gastrectomy - Sun, Dong; Wang, Yanmin; Wei, Meng; Zhang, Zongli; Hu, Sanyuan (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Sleeve gastrectomy (SG) procedure has been proved to improve insulin sensitivity and sustain anti-diabetic effects. Our aim is to co-use several methods to measure insulin sensitivity and investigate the effect of SG on hepatic and peripheral insulin sensitivity at early and long-term stages of postoperation.Methods Thirty 11-week-old male Goto-Kakizaki rats were divided into SG, sham-operated SG (SOSG), and control groups. They were observed before operation and for 36 weeks of postoperation. Insulin tolerance test (ITT) and homeostasis model of assessment for insulin resistance index(HOMA-IR)were used to measure insulin resistance before operations and at 2 and 36 weeks of postoperation; Pyruvate challenge test (PCT) was administrated to assess the gluconeogenesis capability in order to reflect hepatic insulin sensitivity before operation and at 2 and 36 weeks of postoperation; Hyperinsulinemic euglycemic clamps (HIEC) was conducted before operation and at 2 and 36 weeks of postoperation to calculate the endogenous hepatic glucose production (HGP) at the basal and steady-state for evaluation of hepatic insulin sensitivity, and calculate the exogenous glucose infusion rate (GIR) at the steady-state for evaluation of peripheral insulin sensitivity.Results The data showed that compared with rats in the sham and control groups, rats in SG group had 1) significantly lower AUCITT, HOMA-IR and AUC PCT values at 2 and 36 weeks of postoperation, 2) lower basal state HGP, but not steady-state GIR at 2 weeks of postoperation, and 3) significantly different basal and steady-state HGP and steady-state GIR at 36 weeks of postoperation. In addition, the basal and steady-state HGP and the steady-state GIR were significantly different between rats in SG group at 2 and 36 weeks of postoperation.Conclusions This study explored insulin sensitivity of rats after SG by jointly using a variety of techniques. The results showed that SG time-dependently improved the hepatic and peripheral insulin sensitivity.
Keywords: Sleeve gastrectomy; Insulin sensitivity; Goto-Kakizaki rats